The development of early scientific literacy gaps in kindergarten children. Issue 12 (12th August 2020) - Kähler, Jana; Hahn, Inga; Köller, Olaf
ABSTRACT: In times of climate change, worldwide diseases, and the question of sustainable energy, scientific literacy has never been more important. The acquisition of scientific literacy starts in early childhood and depends on children's experiences in learning environments such as the parental home and kindergarten. The Starting Cohort 2 of the German National Educational Panel Study offers longitudinal data on the scientific literacy of 2, 937 children from kindergarten to the third grade of primary school. We used linear latent growth curve models to analyse the data. The results show that the scientific literacy of kindergarten children grew over time and that kindergarten children already differed in their scientific literacy. Especially children from non-German-speaking homes or whose parents had lower levels of education or who came from homes with low cultural capital had a significantly lower level of scientific literacy in kindergarten. A scientific focus in kindergarten, on the other hand, had a positive effect on the scientific literacy of kindergarten children. Moreover, our study did not reveal any interindividual differences in the growth of scientific literacy over time. Thus, our study did not find any evidence to indicate that school had closed the initial gap in children's scientific literacy.